The Effect of Bangpungtongsung-san Extracts on Adipocyte Metabolism - Sang Min, Lee; Byoung Woo, Kim; Ki Rok, Kwon; Tae Jin Rhim; Dong Heui Kim (Korean Pharmacopuncture Institute, 2008)
Objective : The purpose of this study is to investigate the effects of Bangpungtongsung-san extracts on the preadipocytes proliferation, of 3T3-L1 cell line. lipolysis of adipocytes in rat's epididymis and localized fat accumulation of porcine by extraction methods(alcohol and water). Methods : Diminish 3T3-L1 proliferation and lipogenesis do primary role to reduce obesity. So, 3T3-L1 preadipocyte and adipocytes were performed on cell cultures, and using Sprague-Dawley rats for the lipogenesis, and treated with 0.01-1 ㎎/㎖ Bangpungtongsung-san Extracts depend on concentrations. Porcine skin including fat tissue after treated Bangpungtongsung-san Extracts by means of the dosage dependent variation are investigated the histologic changes after injection of these extracts. Results : Following results were obtained from the 3T3-L1 preadipocyte proliferation and lipolysis of adipocyte in rats and histologic investigation of fat tissue. 1. Bangpungtongsung-san extracts were showed the effect of decreased preadipocyte proliferation on the high dosage(1.0㎎/㎖). 2. Bangpungtongsung-san extracts were showed the effect of decreased the activity of glycerol-3-phosphate dehydrogenase(GPDH) on the high dosage(1.0㎎/㎖) and Specially, alcohol extract of Bangpungtongsung -san was clear as time goes by high concentration. 3. Bangpungtongsung-san extracts were showed tries to compare the effect of lipolysis, alcohol extract of Bangpungtongsung-san on the high dosage(1.0㎎/㎖) was observed the effect is higher than water extract. 4. Investigated the histological changes in porcine fat tissue after treated Bangpungtongsung-san extracts, we knew that water extract of Bangpungtongsung-san was showed the effect of lipolysis on the high dosage(10.0㎎/㎖) and alcohol extract of Bangpungtongsung-san was showed significant activity to the lysis of cell membranes in all concentration. Conclusion : These results suggest that Bangpungtongsung-san extracts efficiently induces diminish proliferation of preadipocyte and lipolysis in adipose tissue.